Photocatalytic activity and characterization of sol-gel-derived Cr(III)-doped TiO(2)-coated active carbon composites - Gambhire, A. B.; Lande, Machhindra K.; Mandale, A. B.; Patil, K. R.; Arbad, B. R. (Philosophical Magazine, 2008)
Cr(III)-doped, TiO(2)-coated active carbon (Cr-TiO(2)/AC) were prepared by a sol-gel method. The effect of supports, including TiO(2) and active carbon (AC), on the molecular structure and photocatalytic activity of chromium oxide for complete decomposition of EDTA has been examined with respect to the content of Cr on the catalyst surface. The photocatalytic activity of the Cr-TiO(2)/AC composites was evaluated in the decomposition of EDTA solution under UV irradiation. The results indicate that Cr-TiO(2)/AC has a higher efficiency in decomposition of EDTA than TiO(2), TiO(2)/AC or active carbon. This was attributed to the different functions of active carbon and chromate species. (1) Nanosize TiO(2) particles on composites were not reunited, possible because active carbon retards transformation of anatase into rutile and decreases the crystallite size. (2) Production of high concentrations of organic compound near Cr-TiO(2). (3) Carbon in active carbon causes some of the TiO(2) to reduce to Ti(3+) ions, which prevents electron-hole pair recombination. (4) Formation of polychromate species, with a stronger redox capability, on the surface of TiO(2)/AC. It was found that the addition of Cr to TiO(2) sol could suppress the grain growth of TiO(2) crystals and increase the hydroxyl content on the surface of TiO(2)/AC. The photocatalytic efficiency and activity of the composites remained good, even after three cycles.
Keywords: EDTA; photoactive; sol-gel; Titanium dioxide; XPS

Synthesis and characterization of high surface area CeO2-doped SnO2 nanomaterial - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Shirsat, M. D.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Materials Chemistry and Physics, 2008)
In the present investigation the synthesis and characterization of high surface area CeO2-doped SnO2 nanomaterial has been reported. The material was synthesized by coprecipitation process combined with surfactant incorporating method. The concentration level of Ce (III) additive was varied systematically from 1 to 11 wt.%. After calcinations at500 degrees C,a high BET surface area of 40 m(2)/g was obtained for 7 wt.% CeO2. The effect of variation of sintering temperature (600-800 degrees C/2h) on the particle size and surface area of a CeO2/SnO2 system was investigated. The material obtained was nanocrystalline, having particle size in the range of 10-16 nm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CeO2:SnO2; Nanomaterials; sensors

Synthesis and characterizations of NiTiO(3) nanoparticles prepared by the sol-gel process - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Mandale, A. B.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Philosophical Magazine Letters, 2008)
Nanocrystalline nickel titanate (NiTiO(3)) composite powders were prepared by the sol-gel process combined with a surfactant-assisted template method. The resulting powders were calcined at different temperatures ranging from 150 degrees C to 750 degrees C for 2 h in air. The results revealed that a pure hexagonal phase of NiTiO(3) could be obtained at the low temperature of 750 degrees C. The phase evolution of NiTiO(3) was investigated by X-ray diffraction patterns, Fourier-transform infrared spectroscopy, and X-ray photoelectron spectroscopy. Particle size and morphology were studied by transmission electron microscopy.
Keywords: Nanoparticles; nickel titanate; sol-gel process

Scolecite as an efficient heterogeneous catalyst for the synthesis of 2,4,5-triarylimidazoles - Gadekar, Lakshman S.; Mane, Shivshankar R.; Katkar, Santosh S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2009)
Natural scolecite has been found as an effective catalyst for the one-pot synthesis of 2,4,5-triarylimidazole derivatives via a three component reaction using benzil or benzoin, aldehydes and ammonium acetate. This method provides several advantages such as being environmentally benign, reusable, possessing high yields with increased variations of the substituents in the product and preparative simplicity.
Keywords: 2; 4; 5-Triarylimidazoles; heterogeneous catalyst; Three-component reaction

Scolecite catalyzed facile and efficient synthesis of polyhydroquinoline derivatives through hantzsch multi-component condensation - Gadekar, Lakshman S.; Katkar, Santosh S.; Mane, Shivshankar R.; Arbad, Balasaheb R.; Lande, Machhindra K. (Bulletin of the Korean Chemical Society, 2009)
A facile and efficient synthetic route has been developed for the polyhydroquinoline via four component reactions of aldehydes, dimedone, ethyl acetoacetate and ammonium acetate in the presence of catalytic amount of scolecite in ethanol at 70 degrees C through Hantzsch reaction. This method gives remarkable advantages such as simple work-up procedure. environmentally friendly, inexpensive, non-toxic and recyclable catalyst, shorter reaction time along with excellent yields
Keywords: heterogeneous catalyst; Multicomponent reaction; Polyhydroquinoline; Reusable catalyst

Synthesis and characterization of high-surface-area Ag2O-doped SnO2 nanomaterial - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Shirsat, M. D.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Philosophical Magazine Letters, 2009)
Nanosized tin dioxide-based powders containing silver and palladium oxides have been prepared by coprecipitation reaction. XRD, TEM, and XPS analysis were carried out for investigation of crystalline structure and surface morphology. The best reactive conditions were determined, such as the concentration of the reactants, pH value, surfactants, reaction temperature, and time. The material obtained is nanocrystalline, having a particle size in the range of 5.21-7.42 nm. Effect of doped-Ag2O on the crystal size of the nanoparticles and the influence of the presence of a second dopant (Pd) on the Ag2O/SnO2 matrix was discussed.
Keywords: Ag2O:SnO2; Nanomaterials; XPS

ZnO-beta zeolite: as an effective and eco-friendly heterogeneous catalyst for the synthesis of benzothiazole derivatives - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Vidhate, Kaluram N.; Lande, Machhindra K. (Chinese Chemical Letters, 2010)
A cheap and recyclable ZnO-beta zeolite was used as catalyst for the synthesis of benzothiazole derivatives. This method provides several advantages such as environmental friendliness, short reaction times, high yields, simple work-up procedure and catalyst was successfully reused for four cycles without significant loss of activity. (C) 2009 Machhindra K. Lande. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Benzothiazole; cyclocondensation; heterogeneous catalyst; ZnO-beta zeolite

ZnO-beta zeolite: as an effective and reusable heterogeneous catalyst for the one-pot synthesis of polyhydroquinolines - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Green Chemistry Letters and Reviews, 2010)
ZnO-beta zeolite, an inexpensive and mild catalyst, has been used for the synthesis of polyhydroquinolines in excellent yields from the one-pot four-component condensation of aldehydes, dimedone, ethyl acetoacetate, and ammonium acetate in ethanol at room temperature. The remarkable advantages offered by this method are a green catalyst, mild reaction conditions, simple work-up procedures, much faster reactions, and excellent yield of products. Furthermore, the catalyst could be reused several times keeping its initial activity in recycled reactions.
Keywords: Hantzsch condensation; heterogeneous catalyst; multicomponent; ZnO-beta zeolite

ZnO-beta zeolite mediated simple and efficient method for the one-pot synthesis of quinoxaline derivatives at room temperature - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2010)
A rapid and an efficient one-pot method for the synthesis of quinoxalines catalysed by ZnO-beta zeolite at room temperature is described. This environmentally benign method provides several advantages over methods that are currently employed such as a simple work-up, mild reaction conditions, good to excellent yields, and a process to recover and reuse the catalyst for several cycles with consistent activity.
Keywords: cyclocondensation; Quinoxaline; Room temperature; ZnO-beta zeolite

Degradation of methylene blue via photocatalysis of transition metal-loaded sulfated TiO2 - Gambhire, A. B.; Lande, Machhindra K.; Arbad, B. R.; Rathod, S. B.; Gholap, Ramkrishna S.; Patil, K. R. (Materials Chemistry and Physics, 2011)
Transition metal-loaded nanocrystalline SO42-/TiO2 powders were prepared by sol-gel method. Anatase is found as the active phase in all the samples. Sulfation process clearly stabilizes TiO2 catalyst phase against sintering, maintaining anatase phase and relatively high surface area values with respect to pure TiO2. Wide structural and surface characterization of samples was carried out in order to establish a correlation between the effect of sulfation and metal incorporation on the TiO2 photocatalytic properties. The maximum photocatalytic decomposition of methylene blue solution was achieved with sulfation of TiO2. In addition, incorporation of metal into the structure of SO42-/TiO2 seems to enhance the photocatalytic activity of the samples, which is ascribed to the enlargement of specific surface area, photogenerated carriers separation, light absorption, as well as the higher surface acidity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: nanomaterial; Photocatalytic activity; sol-gel process

Synthesis and characterization of FeTiO3 ceramics - Gambhire, Anil B.; Lande, Machhindra K.; Rathod, Sandip B.; Arbad, Balasaheb R.; Vidhate, Kaluram N.; Gholap, Ramakrishna S.; Patil, Kashinath R. (Arabian Journal of Chemistry, 2016)
Nanocrystalline FeTiO3 ceramics powders were prepared by the sol-gel process combined with a surfactant-assisted template method. The resulting powders were calcined at different temperatures ranging from 150 degrees C to 600 degrees C for 2 h in an air. The results revealed that a pure hexagonal phase of FeTiO3 could be obtained at low temperature, 600 degrees C. The phase evolution of FeTiO3 was investigated by X-ray diffraction patterns (XRD), Fourier-transform infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS). Particle size and morphology was studied by transmission electron microscopy (TEM). (C) 2011 Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Electron microscopy; hexagonal phase; Nanoparticles; sol-gel process; Ti-O bond